Optimizing Curriculum Integration: Development and Validation of the Tool of Integration Practices (TIP) in Health Professions Education - A Mixed Methods Study - Syeda Rabbab Hasan; Madiha Sajjad; Rehan Ahmed Khan (Pakistan Journal of Medical Sciences, 2026)
Objective: Curriculum integration is increasingly used in medical and dental education, yet validated tools to objectively measure integration are limited. Existing frameworks, such as Harden’s ladder, are mostly descriptive and difficult to implement for systematic evaluation. Therefore, this study aimed to develop a valid and reliable tool to assess the level of integration in medical and dental curricula. Methodology: A multiphase mixed-method approach was employed for instrument development. Eight domains representing the integrated curriculum were initially identified through a literature review, each structured on a 5-point scale based on Harden’s integration ladder. Content validity was established via expert review (n = 17), followed by cognitive interviews with faculty (n = 6), and pilot testing with medical and dental faculty (n = 150). Reliability was assessed using Cronbach’s alpha. Results: Content validity resulted in seven domains with a mean content validity index of 0.89 and an average content clarity score of 3.46. Cognitive interviews led to minor adjustments in four items. The final tool demonstrated good reliability (Cronbach's alpha = 0.88). EFA supported a one-factor model, confirmed by CFA (GFI = 0.96, RMSEA = 0.052, normed χ² = 1.4), indicating a good model fit. Conclusion: The Tool of Integration Practices (TIP) demonstrated adequate validity and reliability. It provides a practical, psychometrically sound framework for assessing and comparing curriculum integration practices based on faculty perceptions at the course and program levels in health professions education.